The Role of Education in Economic and Social Development of the Country - Astakhova, Kateryna V.; Korobeev, Alexander I.; Prokhorova, Victoria V.; Kolupaev, Andrey A.; Vorotnoy, Mikhail V.; Kucheryavaya, Evgeniya R. (International Review of Management and Marketing, 2016)
The article said that in the current context, education is an important component of social and economic development. Company represented by the public, corporate, private sector households across the demand for professionals in the goal-setting exercise education. I must say that the accumulated knowledge (scientific, methodological, spiritual) provides a level of education of population, databases and knowledge bases. Implementation possibilities of society is carried out in the research, cultural, industrial, business and other activities in the form of suggestions of experts. In turn, the effectiveness of the educational system and its development is based on three defining principles - accessibility, quality and security. Keywords: education, socio-economic development, state, educational services JEL Classifications: A20; P35